2006
DOI: 10.1063/1.2195782
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an As2S8 stripe waveguide with an optical stopping effect by exposure to ultraviolet irradiation

Abstract: Amorphous As2S8 chalcogenide glass is shown to undergo changes in the refractive index upon exposure to ultraviolet light. This phenomenon is employed to fabricate an As2S8 stripe waveguide, which is shown to be an effective guided mode device with a useful switching functionality based on the photo-optical effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Optical losses are a key parameter for potential applications of chalcogenide‐based thin films. The majority of studies presents optical losses values for chalcogenide waveguide ranging from a few dB/cm up to 10 dB/cm including the middle IR 23–28 . It is worthy to note foregoing work on As 2 S 3 and Ge 33 As 12 Se 55 thin films deposited by ultra fast PLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical losses are a key parameter for potential applications of chalcogenide‐based thin films. The majority of studies presents optical losses values for chalcogenide waveguide ranging from a few dB/cm up to 10 dB/cm including the middle IR 23–28 . It is worthy to note foregoing work on As 2 S 3 and Ge 33 As 12 Se 55 thin films deposited by ultra fast PLD.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies presents optical losses values for chalcogenide waveguide ranging from a few dB/cm up to 10 dB/cm including the middle IR. [23][24][25][26][27][28] It is worthy to note foregoing work on As 2 S 3 and Ge 33 As 12 Se 55 thin films deposited by ultra fast PLD. The waveguides obtained by dry etching gave values of 0.25 and 0.3 dB/cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Photon absorption of these subenergy bands is reported by our optical stopping effect experiments [6,7]. Reported cutoff response time is in milliseconds [8]. The recovery process can be regarded as two processes.…”
Section: Introductionmentioning
confidence: 97%
“…Especially, optical stopping experiments examining the photooptical effect of as-deposited As 2 S 8 films have revealed that the transition process for sublevel electrons occurs by pumping sublevel electrons under irradiation in the band gap region, which does not occur in the amorphous As 2 S 3 . [14] This effect is expected to be applied to the development of the new waveguide devices with the photo-optical effect.…”
Section: Introductionmentioning
confidence: 98%